I4.0 readiness index in electric power distribution in serving modern consumers - Fernando, Very; Hasbullah, Hasbullah; Tommy Wirawanan, Nanda; Bareduan, Salleh Ahmad (2024)
Nowadays, the needs of modern human life are inseparable from the use of electrical energy. The development of eco-friendly technology continues to emerge rapidly to help facilitate daily life, such as electric vehicles (EV), electric stoves, and other modern equipment. A variety of modern equipment will have a technical impact on the distribution of electric power. Perusahaan Listrik Negara (PLN) is a state-own company, as one of the electricity service providers, must serve consumers reliably and efficiently. The existence of modern loads on the consumers side must be addressed with modern electricity supply, such as the preparation of smart grid technology, communication technology between EV charging stations, disturbance management, and efficient asset management. All of that is a readiness index for PLN to serve modern consumers. PLN needs to prepare technology and knowledge in the transformation of industry 4.0. This research helps PLN to assess the readiness of industry 4.0, which we call INDIST 4.0 (Power distribution readiness Index I4.0). The results of this study contain 5 Pillars, 15 Fields as a reference. Assessment for all distribution work areas in Indonesia with a value of 1.9 out of 4, meaning PLN is a newcomer and learner